2022
DOI: 10.3390/biomedicines11010080
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcranial Direct Current Stimulation in Obsessive–Compulsive Disorder Symptoms: A Meta-Analysis and Integrated Electric Fields Modeling Analysis

Abstract: Transcranial direct current stimulation (tDCS) has been showing promising effects for the treatment of obsessive–compulsive disorder (OCD), but there is still no conclusion on its efficacy for this disorder. We performed a systematic review and meta-analysis of trials using tDCS for OCD and a computer modeling analysis to evaluate the electric field (EF) strengths of different electrode assemblies in brain regions of interest (ROIs) (PROSPERO-42021262465). PubMed/MEDLINE, Embase, Cochrane Library and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Additionally, this is also the first randomized-controlled trial that compared the efficacy of two stimulation dosages which is typically needed for establishing clinical efficacy of an intervention. Finally, in comparison to other protocols used in previous studies, a recent metanalysis of tDCS RCTs in OCD showed that protocols that applied cathodal stimulation over the pre-SMA with an extracephalic return electrode delivered stronger electric fields to the circuity involved in OCD in comparison to the other montages (Pinto et al, 2022). None of these tDCS studies targeted the left DLPFC with anodal tDCS.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, this is also the first randomized-controlled trial that compared the efficacy of two stimulation dosages which is typically needed for establishing clinical efficacy of an intervention. Finally, in comparison to other protocols used in previous studies, a recent metanalysis of tDCS RCTs in OCD showed that protocols that applied cathodal stimulation over the pre-SMA with an extracephalic return electrode delivered stronger electric fields to the circuity involved in OCD in comparison to the other montages (Pinto et al, 2022). None of these tDCS studies targeted the left DLPFC with anodal tDCS.…”
Section: Discussionmentioning
confidence: 97%
“…In neuropsychiatric disorders that are characterized by functional brain abnormalities (i.e., hyper-or hypoactivity of specific brain region/s and network/s), it is possible to modify altered brain functions with tDCS, and affect target behavior or cognition (Alizadehgoradel et al, 2020;Fregni et al, 2020;Salehinejad et al, 2022a;Nikolin et al, 2023). In OCD, results of tDCS studies have been mixed so far, and knowledge is still limited about optimal stimulation parameters and efficacy of interventions, such as in other clinical non-invasive brain stimulation scenarios (da Silva et al, 2019;Fregni et al, 2020;Rostami et al, 2020;Silva et al, 2021;Pinto et al, 2022).…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this is also the first randomized-controlled trial that compared the efficacy of two stimulation dosages which is typically needed for establishing clinical efficacy of an intervention. Finally, in comparison to other protocols used in previous studies, a recent metanalysis of tDCS RCTs in OCD showed that protocols that applied cathodal stimulation over the pre-SMA with an extracephalic return electrode delivered stronger electric fields to the circuity involved in OCD in comparison to the other montages [ 19 ]. None of these tDCS studies targeted the left DLPFC with anodal tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…In OCD patients, the pre-SMA is hyperactive, especially during cognitive task performance that requires attentional and inhibitory control [ 28 , 29 ], and is, therefore, a major target of non-invasive brain stimulation treatment [ 17 , 30 , 31 ]. Although the left DLPFC and pre-SMA have been targeted in previous tDCS studies, targeting both regions with anodal and cathodal stimulation respectively has not been reported so far [ 19 , 32 ]. Applying a protocol that can modulate the prefrontal-SMA network and presumably restore physiological abnormalities can have therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%